STRATEGI PENINGKATAN DAYA SAING DALAM BISNIS MINUMAN BOBA: STUDI KASUS PADA MINUMAN BOBA NAYNAY JALAN DURUNG, MEDAN, SUMATERA UTARA - Fitrah, Mutia Salsanu; Karo-Karo , Muhammad Fuazan; Sitorus, Siti Ghadizah Nur; Zainarti, Zainarti (JURNAL EKONOMI AKUNTANSI MANAJEMEN AGRIBISNIS, 2024)
The boba beverage business is experiencing significant growth in the domestic market, but competition in the industry is intensifying. This study aims to identify and analyze strategies that can be used by boba beverage businesses to improve competitiveness. A descriptive qualitative approach is used to examine aspects that affect competitiveness, such as product innovation, marketing strategy, quality management, and adaptation to consumer preferences. The results of this study include SWOT analysis, the resulting strategies include developing taste innovation, building a competitive business system, optimizing technology-based marketing, and improving financial statements and geographic expansion. In addition, the importance of halal certification to improve product competitiveness was highlighted. Although NAYNAY Boba does not yet have halal certification, the government is expected to increase education to MSMEs on the importance of this certification. This research provides practical guidance for boba beverage businesses to compete in an increasingly competitive industry through innovation, technology-based marketing, and halal certification.